2014
DOI: 10.1371/journal.pone.0086510
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Helminth Co-Infections in School and Preschool Children: A Cross-Sectional Study in Magu District, North-Western Tanzania

Abstract: BackgroundMalaria, schistosomiasis and soil transmitted helminth infections (STH) are important parasitic infections in Sub-Saharan Africa where a significant proportion of people are exposed to co-infections of more than one parasite. In Tanzania, these infections are a major public health problem particularly in school and pre-school children. The current study investigated malaria and helminth co-infections and anaemia in school and pre-school children in Magu district, Tanzania.MethodologySchool and pre-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
101
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 54 publications
17
101
8
Order By: Relevance
“…This reported prevalence is higher compared to what has been reported in the nearby district of Sengerema (19.5%) but lower to what was reported in Kilosa district, Central Tanzania (43.4%) [45,46]. This observed difference could be due to differences in the age of study participants, climatic conditions of the study areas which may affect food security as already reported [37] and the difference in the prevalence of malaria which is known to greatly impact on haemoglobin levels [47]. In the current study, anaemia was most prevalent among schoolchildren in the village with low S .…”
Section: Discussionmentioning
confidence: 64%
“…This reported prevalence is higher compared to what has been reported in the nearby district of Sengerema (19.5%) but lower to what was reported in Kilosa district, Central Tanzania (43.4%) [45,46]. This observed difference could be due to differences in the age of study participants, climatic conditions of the study areas which may affect food security as already reported [37] and the difference in the prevalence of malaria which is known to greatly impact on haemoglobin levels [47]. In the current study, anaemia was most prevalent among schoolchildren in the village with low S .…”
Section: Discussionmentioning
confidence: 64%
“…Efforts have been made to document the distribution of Schistosomiasis mansoni in different parts of Tanzania [16, 2426]. However there are still many areas whose prevalence and intensities of infection are yet to be documented.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and GM intensity of S. mansoni based on the Kato-Katz technique on two stool samples were 39.7% and 50.7 epg, respectively. 9 Although the study from 2001 seems to have higher prevalence than this study, the most comparable study is the study from 2006, which have slightly lower prevalence and intensity. Thus, the prevalence and intensity in the area seems not to have decreased at least during the last 8 years.…”
Section: Discussionmentioning
confidence: 46%
“…The slides were transported to the National Institute for Medical Research in Mwanza and examined for S. mansoni eggs. Infections with soil-transmitted helminths were not investigated as Ascaris lumbricoides and Trichuris trichiura have been recorded to be seldom present 8,9 and because eggs of hookworms were not visible because of the time span between preparation and reading.…”
Section: Methodsmentioning
confidence: 99%